Combined microbial and isotopic signature approach to identify nitrate sources and transformation processes in groundwater. (August 2019) - Zhu, Aiping; Chen, Jianyao; Gao, Lei; Shimizu, Yuta; Liang, Dongmei; Yi, Ming; Cao, Lixiang
Abstract: Nitrate (NO3 − ) pollution is a serious problem worldwide. Identification of NO3 − sources and transformation processes in aquifers is a key step in effectively controlling and mitigating NO3 − contamination. In this study, hydrochemical, microbial, and dual isotopic approaches were integrated to elucidate the sources and processes influencing NO3 − contamination in the Pearl River Delta, China. The results showed a severe NO3 − contamination, with 75% of the samples having NO3 − -N concentrations above the WHO standard of 10 mg L −1 . The δ 15 NNO3 - and δ 18 ONO3 - values and a multivariate statistical analysis of hydrochemical data both revealed that manure and sewage were mainly responsible for NO3 − contamination. Biological indicators further demonstrated that, manure and sewage had greater impacts on groundwater quality during the rainy season than during the dry season. Based on the significant relationships of δ 15 NNO3 - and δ 18 ONO3 - with the logarithmic NO3 − concentration (Ln(NO3 − )), denitrification was confirmed to occur in the discharge zone during the rainy season. Proteobacteria, Bacteroidetes, and Planctomycetes were identified as the dominant phyla, and Dechloromonas, Flavobacterium, and Nitrospira were dominant among the denitrifying bacteria in groundwater. The abundance of denitrifying bacteria had significant positive correlations with δ 15 NNO3 - and NO2 − -N during the rainy season, further confirming the occurrence of denitrification during the rainy season. This study showed that dual isotope techniques combined with microbial data can be a powerful tool for identifying the sources and microbial processes affecting NO3 − in groundwater. Moreover, the results can provide useful insights for environmental managers to verify groundwater pollution and better apply remediation solutions. Graphical abstract: Image 1 Highlights: Microbial and isotopic approaches were combined to identify the sources and transformation of NO3 − Manure and sewage were the main sources of NO3 − and had a greater effect on groundwater during the rainy season. Denitrification occurred in the discharge zone during the rainy season. These findings can assist in controlling and mitigating groundwater NO3 − contamination.